EFFORTS TO INCREASE TRIGONOMETRY UNDERSTANDING USING THE DRILL METHOD FOR STUDENTS CLASS X IPA 1 MAN SINTANG - Nuriyansyah Nuriyansyah (Jurnal Scientia, 2023)
Study This is study action class, with objective For increase understanding trigonometry with use Drill method on students class X IPA 1 MAN Sintang. As for the method research used a method study quantitative in study action class through data collection carried out with method observation through gift test to data source . Whereas technique data analysis was performed through analysis quantitative and qualitative . As for the results research obtaine. A application learning drill method can increase sense of responsibility answer to assignments given. Obtained also 65% of students including Very happy category, 35% of students including category happy, no There is less students _ happy and not There is students who don't like with new learning just followed. Besides that results test cycle 1 obtained an average result Study student by 84 with standard deviation 17.23, meanwhile results test Cycle 2 obtained an average result Study student by 93 with standard deviation 9,8. Percentage completeness cycle 1 is 79% and cycle 2 is 100%. Condition This show exists enhancement results Study student after done learning with drilling method .